Was leistet Lehrdichtung?: Neue Perspektiven auf das Motiv der Himmelsreise in Manilius’ "Astronomica“ - Kuhn-Treichel, Thomas (Hermes, 2020)
Concentrating on the motif of the heavenly journey in Manilius’s “Astronomica”, this contribution raises the question as to whether the combination of poetry and teaching in didactic poetry can bring about intrinsic advantages. It is argued that the motif does not just transport the poet’s claim to have privileged access to knowledge, but can also have objective functions in the transfer of knowledge. According to recent cognitive studies, perception is deeply rooted in the sensorimotor system; in light of these insights, the motif can be seen to make the subject of instruction more experienceable for the recipients as it depicts bodily interaction with the cosmos.